(untitled) - Ana Paula Bartmann; Josemir W. Sander (Arquivos de Neuro-Psiquiatria)
Epilepsy affects between 5 and 10 people in a 1,000 and carries considerable morbidity and premature mortality. The complex inheritance pattern of a lowered seizure threshold is not fully understood but is likely to be polygenic. In the majority of people with epilepsy, we do not understand the pathophysiology, how a seizure is triggered, and how it can be prevented. In the centennial year of the discovery of the antiepileptic properties of phenobarbital, we have over 20 antiepileptic drugs; however, none have dramatically changed the long-term prognosis of the condition. The cascade of events triggering epilepsy is likely to vary greatly among individuals. The hope for the future is a shift of paradigm away from the symptomatic approach that currently exists. Indeed, once epileptogenesis is fully understood, treatment can be targeted at specific mechanisms, and then we will have truly disease-modifying therapies.